Pengaruh Kecerdasan Emosional terhadap Kepuasan Kerja yang Dimediasi oleh Efikasi Diri - Herdiman; Tirtoprojo, Susanto (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2024)
This research investigates the influence of emotional intelligence on job satisfaction which is mediated by self-efficacy. This research was conducted on state elementary school teachers in Nanga Wera Village, Wera District, Bima Regency. Data was collected using an online survey method. The respondents in this investigation were educators who taught at state primary educational institutions in Nanga Wera village, Wera subdistrict, Bima Regency. The number of respondents to this study was 52 people and were identified using an online questionnaire. Data analysis was carried out using a statistical regression approach using SmartPLS software. The research results show that there is a significant positive influence between teacher emotional intelligence and job satisfaction, and self-efficacy has a significant mediating influence on how job satisfaction and emotional intelligence are related.